Synthesis of Chitosan Silica Membrane from Petung Bamboo (Dendrocalamus asper) Leaves and Its Application as Pb(II) Metallic Adsorbent - Hasri, Hasri; Pratiwi, Diana Eka; Safitri, Isriyanti; Negara, Satria Putra Jaya (Indonesian Journal of Chemistry, 2024)
Membrane synthesis through a phase inversion method using chitosan and sodium silicate solutions has been conducted. This research aims to characterize the silica chitosan membrane (SCM) of petung bamboo leaves and determine the synthesized product's adsorption capacity for Pb(II) ions. The XRF characterization showed the silica content of petung bamboo leaves with a percentage of 78.03%. SEM analysis before adsorption is around 13.0 μm, and the pore diameter after adsorption is around 9.7 μm. The results of adsorption analysis of Pb(II) metal using AAS showed that the SCM variation A at an initial concentration of 10.0000 ppm Pb(II) metal adsorbed was 9.8101 ppm, and at an initial concentration of 25.0000 ppm Pb(II) metal was 22.3421 ppm. The variation B at an initial concentration of 10.0000 ppm Pb(II) metal adsorbed was 9.8870 ppm and at an initial concentration of 25.0000 ppm Pb(II) metal adsorbed was 23.5806 ppm. The variation C at an initial concentration of 10.0000 ppm Pb(II) metal adsorbed was 9.9639 ppm, and at an initial concentration of 25.0000 ppm Pb(II) metal was 24.1855 ppm. The results of this research conclude that the highest SCM adsorption power is variation C (2%:22.95%) with a percentage of 99.63%.